Self-esteem as a mediator between personality traits and body esteem: path analyses across gender and race/ethnicity. - Małgorzata Skorek; Anna V Song; Yarrow Dunham (PLoS ONE, 2014)
Prior literature examines the direct relationship between personality traits and body esteem. This article explores the possibility that self-esteem mediates this relationship. 165 undergraduate women and 133 men (age 18-21; 42.6% Hispanic, 28.9% Asian, 28.5% Caucasian) completed items measuring personality traits (Big Five), self-esteem, and body esteem. Path analyses were used to test for mediation. The analyses confirmed that in both men and women self-esteem mediated the relationship between three personality traits and body esteem: higher levels of conscientiousness, emotional stability, and extraversion were associated with higher self-esteem and consequently higher body esteem. Once self-esteem was included in the model the relationships between personality traits and body esteem were not significant, suggesting full mediation. In addition, the analyses revealed several racial/ethnic differences. In Asian American participants, self-esteem mediated the relationship between conscientiousness and body esteem and between emotional stability and body esteem. In Hispanic Americans, self-esteem mediated the relationship between conscientiousness and body esteem and between extraversion and body esteem. And in Caucasian Americans, self-esteem mediated the relationship between emotional stability and body esteem and between extraversion and body esteem. The most important contribution of this study is evidence for an indirect relationship between personality traits and body esteem, with this relationship being mediated by self-esteem. This has important implications for the study of personality and eating disorders in young adults, most particularly implying a need for more emphasis on self-esteem as a predictor of body image problems.